2006
DOI: 10.1002/jctb.1646
|View full text |Cite
|
Sign up to set email alerts
|

Studies in mineralization of aqueous aniline using Fenton and wet oxidation (FENTWO) as a hybrid process

Abstract: A hybrid process for mineralization of aqueous aniline using Fenton and wet oxidation (FENTWO) is studied. It is important to have maximum conversion of 'N' atoms from the waste to N 2 . The conversion of input 'N' atoms in aniline to N 2 was 15% during wet oxidation without the Fenton process and was improved to 50% with the Fenton process. Therefore, a hybrid process of Fenton followed by wet oxidation was studied for mineralization of the aqueous aniline stream. The parameters for the Fenton process were op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…It has been proven, by indirect analysis of changing pH during the reaction process, that basic pH in raw wastewater (about 8.5) become slightly acidic in treated wastewater (about 6.5), which can only be due to the formation of short-chain car- boxylic acids. Other studies have also reported similar results in terms of biodegradability index improvement by WAO system for other type of wastewater (Tembhekar et al, 2015;Gunale and Mahajani, 2007;Malik et al, 2014;Weber et al, 2015;Yang et al, 2010). In conclusion, it can be expressed that the WAO process as a pretreatment can provide suitable conditions for biodegradation of treated PCW.…”
Section: Mineralization and Biodegradability Studies Of Treated Pcwsupporting
confidence: 70%
See 1 more Smart Citation
“…It has been proven, by indirect analysis of changing pH during the reaction process, that basic pH in raw wastewater (about 8.5) become slightly acidic in treated wastewater (about 6.5), which can only be due to the formation of short-chain car- boxylic acids. Other studies have also reported similar results in terms of biodegradability index improvement by WAO system for other type of wastewater (Tembhekar et al, 2015;Gunale and Mahajani, 2007;Malik et al, 2014;Weber et al, 2015;Yang et al, 2010). In conclusion, it can be expressed that the WAO process as a pretreatment can provide suitable conditions for biodegradation of treated PCW.…”
Section: Mineralization and Biodegradability Studies Of Treated Pcwsupporting
confidence: 70%
“…According to Erjavec et al (2013), in the catalytic WAO process, increasing the reaction time to 90 h and the reaction temperature to 210 • C, the total BPA destruction was obtained (Erjavec et al, 2013). Other review studies have reported that in the CWAO process, the increase of the reaction time had a positive effect on the decomposition of toxic organic matter (Erjavec et al, 2013;Arena et al, 2015;Kim and Ihm, 2011;Al-Momani et al, 2002;Gunale and Mahajani, 2007). So, it can be concluded that the increase of the reaction time improved significantly the mineralization of the PCW effluent.…”
Section: The Effect Of Reaction Timementioning
confidence: 94%
“…Although chemical precipitation and coagulation are effective in removal of fluoride and SS, they are largely ineffective in removing COD Cr , dissolved organic carbon (DOC) and colour. On the other hand Fenton oxidation has been demonstrated to be quite effective in treating different industrial waste‐waters 14–24. Fenton oxidation tends to destroy the recalcitrant organic chemicals in the waste‐water, resulting in the removal of COD Cr , DOC and colour.…”
Section: Introductionmentioning
confidence: 99%